Assessing the Suitability of Surface Water and Groundwater for Irrigation Based on Hydro-chemical Analysis: A Study of the Mayurakshi River Basin, India. Issue 15 (January 2022) - Ghosh, Susmita; Sarkar, Biplab; Islam, Aznarul; Shit, Pravat Kumar
The present work aims to investigate the hydro-chemical properties of the surface and groundwater of the Mayurakshi River Basin, India for assessing their irrigation suitability with respect to irrigation hazards. The study involves 72 water samples classified as 48 surface water samples (pre-monsoon: 24, post-monsoon: 24) and 24 groundwater samples (pre-monsoon: 12, post-monsoon: 12). The study of ionic chemistry reveals that the cations of both the surface water and groundwater are in the order of Ca 2+  > Mg 2+  > Na +  > K + while the anions are in the order of Cl −  > SO4 2  > PO4 3−  > NO3 − . Moreover, as per the U.S. Salinity Laboratory Staff classification of irrigation, ~ 41.67% of the groundwater samples belong to the C3S1 category indicating high salinity and low sodicity hazard while ~ 33% of samples of surface water fall into the field of C1S1 category representing low salinity and low sodicity hazard. Besides, regarding the specific irrigation hazard, percent sodium and soluble sodium percentage have also portrayed the groundwater vulnerability to sodium while the surface water is observed free from this kind of hazard. Similar findings have also been retained for magnesium hazard and potential salinity hazard. Moreover, regarding the seasonality of the hazards, the post-monsoon season has depicted a higher level of irrigation hazards compared to the pre-monsoon season. The study finds that the general evolution of groundwater hydrochemistry and the suitability of water for irrigation is principally governed by carbonate weathering. Moreover, anthropogenic activities such as sand mining, stone crushing, and the development of brick kiln industries are found to play an important role in irrigation suitability.